Is the concept of SLD still that essential? - Massidda, Geremia (Quaderni di Psicologia Clinica, 2022)
This paper proposes a critical reading of the notion of specific learning disorder (SLD), with a brief excursus of its history and the literature on the subject. Historically, the concept of SLD has the merit of being the foundation for the innovative law 170/10. However, from the outset, this law was incomplete, as it neglets all other special educational needs (SEN). Art. 3 of this law indicates the need to put into place preventive strategies to identify and help, through targeted educational interventions, children at risk of SLD before subjecting them to measurement of their neuro-cognitive characteristics. The preventive strategies outlined in the law replicate, in a reduced way, the strategies of so-called “RTI Method”, therefore they can be advantageously implemented through a more complete integration of the mentioned RTI Method into the school efforts to address SLD problems.
Keywords: SLD; SEN; learning difficulties; RTI Method; school integration